Operators with Property (E) as Concerns Numerical Analysis and Visualization. (17th August 2020) - Usurelu, Gabriela Ioana; Bejenaru, Andreea; Postolache, Mihai
Abstract: In this paper, we study a Thakur three-step iterative process in the new context of generalized nonexpansive mappings enriched with property ( E ). A uniformly convex Banach space is used as underlying setting for our approach. In order to emphasize our results we offer an example of a mapping on R 2 endowed with property ( E ) that exceeds the well known class of Suzuki mappings. By connecting the Thakur iterative process (and many other iterations) with this example, we perform a comparative numerical experiment. This brings to light a new method that allows the visualization of some convergence behaviors.